Community-oriented Oral Health Promotion for Infants in Jerusalem: Evaluation of a Program Trial - Harold D. Sgan-Cohen, DMD, MPH: lvonne Kleinfeld Mansbach, MPH, PhD; Dana Haver, RDH; (Blackwell Synergy, 2001)
This study sought to measure the effect of a community health education program on reported infants’ bottle-feeding practices and infants’ toothbrushing behavior, with or without distribution of toothpaste and toothbrushes.